KONSEP DAN TAHAPAN PEMBENTUKAN PROGRAM - Utami, Sindy Khumairoh; Meliza, Indah; Yanti, Sella Juli; Putri, Yecha Febrieanitha (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The parenting program is a form of activity carried out to harmonizecare and education of children at school and at home. Get an important parenting programparents to increase knowledge related to parenting in accordance with their growth and developmentchild development. The purpose of the parenting program is to increase the knowledge and skills of parents in carrying out the care, upbringing, and education of children in their own families with the foundation of good character.Parenting is also a series of decisions about socialization in children which includes what parents must do so that children are able to take responsibility and contribute as a member of society. being a caregiver, this is how parents should explain to children how children can have a high responsibility for all the things they do. the family always supports the activities the child does as long as it is a good thing to do. Character can also be influenced by the heredity of a child's behavior, often not far from the behavior of his father and mother. Apart from that, the environment, both the social environment and the natural environment, also forms the character. Referring to the various meanings and definitions of these characters.